Great Theorists of Central European Integration in Serbia - Cvetkovic, Srdjan; Šarenac, Danilo (Great Theorists of Central European Integration, 2023)
This chapter presents the biographies of six important Serbian intellectuals who worked in Serbia and Vojvodina during the 19th and 20th centuries: Ilija Garašanin, Svetozar Miletić, Vladimir Jovanović, Dimitrije Mitrinović. Slobodan Jovanović, and Borislav Pekić. Ilija Garašanin was a Serbian statesman who served as a Minister of the Police and Army in the Principality of Serbia. He strongly believed in establishing a modern bureaucracy and maintaining law and order and was the creator of the first written Serbian national programme. Svetozar Miletić was a temperamental and skilled orator. He was a liberal who played a very important role in the national awakening of the Serbs in Southern Hungary in 1848. He stressed the need to support citizens’ individual liberties. Vladimir Jovanović was seen as the most educated intellectual in Serbia in his time. This liberal believed in the coexistence of ideas of national liberation and struggles for citizens’ rights. Dimitrije Mitrinović was a Serbian avant-garde critic, theorist, philosopher, essayist, poet, and translator. He was one of the most unusual intellectuals in the Balkans at the beginning of the 20th century. He was alternately seen by his contemporaries as a charlatan and mystic but also as a visionary of a united Europe and the ‘new man’. Slobodan Jovanović was a lawyer, historian, and politician known for his ideas about the reform of the Kingdom of Yugoslavia and the implied establishment of ‘a fair border’ between Serbs and Croats. Borislav Pekić was another famous Serbian writer, intellectual, and politician. As a writer, he fought for the democratisation and Europeanisation of Serbia. He reconciled national, democratic, and European concepts in the Serbian tradition and asserted that they are not in opposition but should instead be interwoven and integrated.KEYWORDS: Integration, intellectual, Yugoslav idea, Serbia, United Europe, Ilija Garašanin, Svetozar Miletić, Vladimir Jovanović, Dimitrije Mitrinović, Slobodan Jovanović, Borislav Pekić.